Influence of Wholebody Extreme Aerocriotherapy on Functional State of Cardiovascular System - OnishÑhenko, Viktoriya O. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 184.